An investigation into the management of bilateral leg amputees. Issue 6293 (12th September 1981) - Van De Ven, C M
Abstract : Patients with bilateral high level amputations of the legs are rarely functionally independent after their discharge from hospital. Eighty bilateral amputees were visited by a research physiotherapist, and information was obtained on their family circumstances, accommodation, mobility, and prostheses. A second questionnaire was completed by hospital staff on medical condition, assessments, rehabilitation, and total overall management. The results showed that mobility was severely restricted; out of the 80 patients visited, only 65 could manoeuvre wheelchairs and 23 use prostheses. Accommodation presented difficulties: 34 homes had steps inside and 40 had steps outside. Of the 80 patients seen, 60 could not cope in the bath while 33 were unable to use the lavatory. Assessments and rehabilitation were lacking. There appeared to be little overall management, and hospital staff made only 36 visits to the patient's accommodation before discharge.